2021
DOI: 10.3390/su132011364
|View full text |Cite
|
Sign up to set email alerts
|

Limits of Negotiable Developer Obligations

Abstract: Many local authorities apply public value capture on new developments to cover the costs of additional public services. The development obligations (DO) they apply can be either negotiable (NDO) or non-negotiable (NNDO). This article examines the limits of NDOs by comparing three national case studies according to the basic principles of proportionality, causality, connection, and lack of transparency for developers. Well-developed building land models and a delineation of applicable cost types offer more tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Furthermore, Turk [17] found that NDOs in Turkey have a higher public value capture capacity than N-NDOs. However, he also found that they are coupled with lower levels of transparency and accountability resulting in increased uncertainty and risk for developers, which has been observed in other national contexts as well [7,18].…”
Section: Negotiable Developer Obligationsmentioning
confidence: 85%
See 4 more Smart Citations
“…Furthermore, Turk [17] found that NDOs in Turkey have a higher public value capture capacity than N-NDOs. However, he also found that they are coupled with lower levels of transparency and accountability resulting in increased uncertainty and risk for developers, which has been observed in other national contexts as well [7,18].…”
Section: Negotiable Developer Obligationsmentioning
confidence: 85%
“…The use of indirect instruments in some empirical contexts might be difficult to connect directly to capturing unearned private land value gains, and may instead be capturing value increments caused by the landowners. For this reason, some have suggested that public value capture should more broadly refer to any instrument that captures any increase in land and building value, and not solely unearned land value increments [6,7], a perspective adopted here as well. As a result of being more pragmatic, flexible and adaptable in practice, indirect instruments are more common than direct instruments.…”
Section: Public Value Capture Instrumentsmentioning
confidence: 99%
See 3 more Smart Citations